2020
DOI: 10.1093/neuonc/noaa260
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated stereotactic re-irradiation with pembrolizumab and bevacizumab in patients with recurrent high-grade gliomas: results from a phase I study

Abstract: Background Radiotherapy may synergize with programmed death 1 (PD-1)/PD-1 ligand (PD-L1) blockade. The purpose of this study was to determine the recommended Phase II dose, safety/tolerability, and preliminary efficacy of combining pembrolizumab, an anti-PD-1 monoclonal antibody, with hypofractionated stereotactic irradiation (HFSRT) and bevacizumab in patients with recurrent high grade gliomas (HGGs). Methods Eligible subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 28 publications
3
66
0
Order By: Relevance
“…Treatment was well tolerated, with only one discontinuation due to grade 3 transaminases elevation. ORR in the bevacizumab naïve and bevacizumab resistant cohorts was 83% and 62.5%, respectively [ 40 ]. Median PFS was 7.92 and 6.54 months, and median OS was 13.45 and 9.3 months in bevacizumab naïve and bevacizumab resistant patients, respectively [ 40 ].…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment was well tolerated, with only one discontinuation due to grade 3 transaminases elevation. ORR in the bevacizumab naïve and bevacizumab resistant cohorts was 83% and 62.5%, respectively [ 40 ]. Median PFS was 7.92 and 6.54 months, and median OS was 13.45 and 9.3 months in bevacizumab naïve and bevacizumab resistant patients, respectively [ 40 ].…”
Section: Clinical Datamentioning
confidence: 99%
“…ORR in the bevacizumab naïve and bevacizumab resistant cohorts was 83% and 62.5%, respectively [ 40 ]. Median PFS was 7.92 and 6.54 months, and median OS was 13.45 and 9.3 months in bevacizumab naïve and bevacizumab resistant patients, respectively [ 40 ]. In a phase I/II clinical trial evaluating the combination of HFSRT with durvalumab for recurrent GBM (NCT02866747), one dose-limiting-toxicity (DLT) was reported among six patients (grade 3 immune-related vestibular neuritis).…”
Section: Clinical Datamentioning
confidence: 99%
“…Patients with recurrent HGG included in this modelling study (n=16) were treated at the Moffitt Cancer Center, FL between August 2015 and March 2018 as part of a phase I clinical trial (NCT02313272, 05/12/2014) 8 . All patients provided written consent and the treatment protocol was approved by the institutional review board (IRB study #: Pro00014674 and # 00000971).…”
Section: Patient Cohortmentioning
confidence: 99%
“…This study demonstrated safety in terms of adversarial side effects for this particular protocol. Although efficacy was not the primary endpoint, the response results were promising; yet median time to progression remained below one year 8 . In this trial, HFSRT was given in doses with maximum log cell kill intent over one week (consistent with current practice and trials for recurrent HGG re-irradiation studies 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation